2014
DOI: 10.1111/pme.12429
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial Trigger Points in Patients with Whiplash-Associated Disorders and Mechanical Neck Pain

Abstract: Active MTPs are more prominent in WAD than MNP and related to current pain intensity and size of the spontaneous pain distribution in whiplash patients. This may underlie a lower degree of sensitization in MNP than in WAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 48 publications
(69 reference statements)
0
23
0
1
Order By: Relevance
“…12 Manual therapy includes stretching techniques for superficial cervical muscles, 13 passive mobilization through physiological and accessory movements, 14 massage and fascial manipulation or release. 15,16 An alternative conservative treatment for NP is Global Postural Reeducation (GPR), a therapeutic strategy developed by Philippe-Emmanuel Souchard. 17 It is based on a central concept that postural muscles are organized to act in concert with each other as "muscle chains" located anterior and 5 posterior to the spine.…”
Section: Introductionmentioning
confidence: 99%
“…12 Manual therapy includes stretching techniques for superficial cervical muscles, 13 passive mobilization through physiological and accessory movements, 14 massage and fascial manipulation or release. 15,16 An alternative conservative treatment for NP is Global Postural Reeducation (GPR), a therapeutic strategy developed by Philippe-Emmanuel Souchard. 17 It is based on a central concept that postural muscles are organized to act in concert with each other as "muscle chains" located anterior and 5 posterior to the spine.…”
Section: Introductionmentioning
confidence: 99%
“…From this review we identified evidence of the following dysfunction,: thoracic spine pain in acute/sub-acute/chronic WAD ranging from minor injuries to more severe (WADIII) presentations [11,14,17,32,33,43,50,52,58,62]; chest pain in acute/sub-acute/chronic WAD [11,17,52,53]; postural changes [44,61] and reduced chest/thoracic mobility in CWAD [61]; thoracic outlet syndrome in CWAD [31,35,36,47,51]; involvement of the brachial plexus at all stages and across all levels of WAD severity [12,46,55,57,59]; muscle dysfunction in the form of the following: 1) heightened activity of the sternocleidomastoid during neck flexion [12,56], 2) delayed onset of serratus anterior during arm elevation at the chronic stage in mild WAD [45] and 3) a high prevalence of myofascial pain and trigger points in the scalene muscles [40,41], sternocleidomastoid [37,40,41] and mid/lower fibres of trapezius [16] within the subacute and chronic stages and across different levels of severity.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Myofascial pain and trigger points. Myofascial trigger points are highly prevalent in WAD with estimates ranging between 48-64% [16,37,40]. Muscles that have been investigated include the middle/lower trapezius [16], scaleneus medius [40,41] and sternocleidomastoid [37,40,41], all with similar prevalence levels.…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…One source of shoulder pain can be myofascial trigger points (MTrPs), which are localized, hyperirritable points that are associated with palpable nodules in taut bands (TBs) of muscle fibers . MTrPs can be classified into active and latent .…”
Section: Introductionmentioning
confidence: 99%